Metasurface cylindrical vector light generators based on nanometer holes. (18th December 2019) - Lv, Haoran; Lu, Xiaoqing; Han, Yuansheng; Mou, Zhen; Zhou, Changda; Wang, Shuyun; Teng, Shuyun
Abstract: A kind of metasurface cylindrical vector light (CVL) generator in the visible region is proposed. This kind of CVL generator consists of nanometer holes etched on silver film, and it can change any linearly or circularly polarized light into the CVL in nanoscale. The order of the generated CVL is controlled by the rotation of the holes and its polarization state changes with the incident polarization condition. The base transformation theory guides is used to design the metasurface. The numerical simulations for the transmission of the proposed CVL generators confirm the validity of the theoretical predictions, and they also provide the available parameters for practical metasurface devices. The experimental results verify the performance of the proposed metasurface CVL generators. This kind of vector light generator has the advantages of thin and compact structure, polarization multiplexing and convenient manufacture. This work paves a new path for designing the miniature devices to generate the vector light field and it will promote the applications of polarization devices in optical integration and micro-manipulation.